ISOLASI DAN IDENTIFIKASI SENYAWA FENOL DARI EKSTRAK METANOL BIJI PEPAYA (Carica Papaya Linn) - Olii, Helda; Musa, Weny J.A; Paputungan, Mardjan (Jurnal Sainstek, 2013)
Isolation and Identification Fenol Compound of Papaya Seed (Carica Papaya L). The objective of this sresearch is to isolate and identify the compound from Papaya Seed (Carica Papaya L). There are around 600gr of Papaya Seed (Carica Papaya L) pollen mixed with methanol solution and produced 4,6 L of solution then evaporated and produced 88, 89 gr thick extract. Separation by chromatography column got 7 fractions (H1 -H 7). Fraction H7 continued by purify tested by using dimension KLT 1 and KLT 2 produced 1 spot. The chemistry tested shows positively to fenol and alkaloid. Pure isolate continued by spectrometry analysis UV-Vis and IR. The result of spectopometry from isolate showed that there are an absorption on wave length 262, 5 nm tape 1 and 213, 5 nm tape 2. Identification by IR shows that there are cluster function O-H bond, C-H aromatic, C-H Aliphatic, C=C, C=O, and C=O. from both analysis and chemistry tested pure isolate compound is Fenol compound.